TEACHERS’ QUESTIONS IN ENGLISH CLASSROOM OF GRADE EIGHT IN JUNIOR HIGH SCHOOL - Anting Mas Tessa Samosir; Anni Holila Pulungan (Universitas Negeri Medan, 2022)
The goal of this study was to describe teachers’ questions in Englishclassroom and the students’ responses toward the questions. In a classroom context,typically teachers ask a lot of questions. The research indicated that whether or not ina content classroom or in language classroom teachers asked many questions. Thestandard pattern in the classroom was one in which the teacher asked questions, oneor more students responded to the question and then the teacher evaluated theresponses. Thus in term of a classroom context, a questioning session happenednaturally as a process of learning. A descriptive qualitative design was used in thisstudy. The data of this research was collected from classroom observation of twoEnglish teachers (RP & SG) and two classes (VIII-3 & VIII-5) of SMP N 5 Percut SeiTuan. This research dealt with teachers’ questions of grade eight in junior high schoolEnglish classroom. This study conducted to answer questions what types of questionsdo the teacher tend to use in the daily practices of teaching in the English learningand how do the students responded to the questions. The finding indicated that in thequestions types, display questions were highly uttered by the teacher rather thanreferential questions. As the purposes of learning English in a junior high schoolcontext is to engage student to communicate in spoken, all the questioning functionsare related to eliciting information, checking students’ understanding the lesson beingtaught and encouraging them to participate more in the classroom. Therefore, thequestions posed by the teacher were highly distributed. The study is beneficial forboth teacher and student in English language classroom. Questioning and answeringsession happen to force students to speak English even though it is only telling whatthey know about the lesson. It also beneficial for teachers who facilitates students’language ability through asking effective question in an effective way.